1983
DOI: 10.1073/pnas.80.17.5305
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of metabolic cooperation by cigarette smoke condensate and its fractions in V-79 Chinese hamster lung fibroblasts.

Abstract: This study was performed to determine the usefulness of the intercellular metabolic cooperation assay for analysis of a complex mixture and to compare the results obtained with previously conducted in vivo tumor promoter assays. One hundred 2R1 cigarettes were smoked according to Federal Trade Commission guidelines and the resulting condensate was separated into a water/methanol-soluble fraction (which was further partitioned into acidic and basic components) and an organic solvent-soluble fraction (which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…If, as has been shown with many known teratogens, tumor promoters and reproductive toxicants (see reviews Trosko and Chang, 1984;also Aylsworth et al, 1984;Rubinstein et al, 1984;Hartman and Rosen, 1983;Malcolm and Mills, 1984;Welsch and Stedman, 1984), inhibition of gap junction-mediated intercellular communication contributes in part to teratogenesis, tumor promotion and reproductive dysfunction, then the results of this study have several implications.…”
Section: Discussionmentioning
confidence: 99%
“…If, as has been shown with many known teratogens, tumor promoters and reproductive toxicants (see reviews Trosko and Chang, 1984;also Aylsworth et al, 1984;Rubinstein et al, 1984;Hartman and Rosen, 1983;Malcolm and Mills, 1984;Welsch and Stedman, 1984), inhibition of gap junction-mediated intercellular communication contributes in part to teratogenesis, tumor promotion and reproductive dysfunction, then the results of this study have several implications.…”
Section: Discussionmentioning
confidence: 99%
“…∞: when dividing integer with 0 as in the case when expressing ratio where XIC value of control modified peptide is 0 On the other hand, we found that both liquids negatively affected metabolic cooperation as assessed by metabolic HPRT assay, indicating impaired intercellular communication between wild type and HPRT deficient cells. The metabolic cooperation assay has been historically used to study gap junctional intercellular communication as it requires cell-to-cell contact and has also shown a level of correlation with carcinogenesis [54][55][56][57]. Cigarette smoke condensate has been previously shown to disrupt metabolic cooperation in V79 cells [55], but so far there were no reports on using this assay for studying e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic cooperation assay has been historically used to study gap junctional intercellular communication as it requires cell-to-cell contact and has also shown a level of correlation with carcinogenesis [54][55][56][57]. Cigarette smoke condensate has been previously shown to disrupt metabolic cooperation in V79 cells [55], but so far there were no reports on using this assay for studying e-cigarettes. Biological consequences of impaired intercellular communication are broad and this effect of e-cigarettes remains to be studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…One likely explanation is that the chemicals in cigarette smoke act more as tumor promoters by selecting preexisting mutated p53±containing cells (the``initiated'' cells). Several years ago, chemicals from cigarette smoke were shown to inhibit gapjunctional intercellular communication (GJIC), a proposed cellular mechanism in tumor promotion [32].…”
mentioning
confidence: 99%